EFEKTIVITAS KONSENTRASI DAN WAKTU MASERASI EKSTRAK DAUN BELUNTAS (Pluchea indica L.) TERHADAP PERTUMBUHAN Streptococcus pyogenes - Ismi Yulandari, Siti; Dermawan, Asep; Kurniati, Iis; Iin Nur Indra, Asep (Jurnal Kesehatan Siliwangi, 2024)
One of the most common diseases in Indonesia, namely pharyngitis, is caused by Streptococcus pyogenes. Inappropriate treatment of pharyngitis with antibiotics can result in bacteria that are resistant to antibacterials. Therefore, herbal plants that are effective as natural antibacterials are needed, such as beluntas leaves (Pluchea indica L.) to prevent this. Apart from that, the right method is needed so that the contents of the beluntas leaves can be attracted properly. The aim of this research was to determine the effective concentration and maceration time of beluntas leaf extract in inhibiting the growth of S.pyogenes. This research used varying maceration times of 24 and 72 hours. Then, from each variation of maceration time, beluntas leaf extract was made in concentrations of 5%, 10%, 15%, 20%, and 25%.  Beluntas leaf extract was tested for its inhibitory power against S.pyogenes using the Kirby Bauer method. The data obtained was the diameter of the inhibitory power of beluntas leaf extract on the growth of S.pyogenes, then the data was processed statistically using the Kruskal-Wallis test and a further test, namely the Post Hoc Test. The results of this research were that beluntas leaf extract which was macerated for 72 hours with a concentration of 20% and 25% had an average diameter of inhibition against S.pyogenes of 9.04 mm and 12.71 mm. Therefore, a maceration time of 72 hours with a concentration of 25% is effective in inhibiting the growth of S.pyogenes.